AN ANALYISIS OF TECHNIQUES USED IN TRANSLATION OF ARTICLES IN BBC DWI BAHASA INTO BAHASA INDONESIA - Fahmi Jagat Pamungkas (Journal of English Education Program (JEEP), 2019)
This is a study about an analysis of techniques translation in BBC Dwi Bahasa articles. The aims of this study is to analyze the kind of translation techniques used and the most dominant techniques used by the translator in translating BBC Dwi Bahasa articles into Bahasa Indonesia. The Translation Techniques used in this study are adapted from Molina and Albir in 2002.The method applied in the study is descriptive qualitative. The sources of the data in this study are text articles in BBC Dwi Bahasa. The population was all of articles in BBC Dwi Bahasa. Four articles used as the samples to find out the translation techniques used. The writer used content analysis in finding out the data from the text article. From these data identify the techniques of translation, then based on the translation techniques used can be concluded that the result of the study showed that there were eight translation techniques used by the translators, they are : adaptation with 3 data (3,15%), amplification with 4 data (4,21%), pure borrowing with 7 data (7,36%), naturalized borrowing with 23 data ( 24,21%), calque with 6 data (6,21%), literal translation with 7 data (7,36%), modulation with 16 data (16,85%), reduction with 13 data (13,68%) and transposition with 16 data (16,84%). Borrowing translation was the most dominant techniques used in BBC articles especially naturalized borrowing. Based on the result of the study it is hoped that such translation techniques can be considered by those who want to be the translators. Keywords: translation, translation techniques,source language and target language.